Implementasi Evaluasi Formatif dan Sumatif Dalam Pembelajaran Fikih di Mts Al-Mukarrom Ponorogo - Hilda Rilawati Khasanah; Nurul Malikah; Ida Martafia Putri; Iffah Rahma Saniyah; Ihdaa Sabiila Faradisi; Imro'atus Azizah; Intan Muslimah (https://ejournal.insuriponorogo.ac.id/, 2024)
In line with the objectives of Fiqh education, which aim to equip students with a deep understanding of Islamic laws and their implementation, so they can apply them in their daily lives, instilling Fiqh values in students from an early age is crucial. This is especially important in an increasingly modern era, as it forms the most fundamental foundation in their growth and development related to Islamic laws. The objectives of this research are: (1) To describe the implementation of formative evaluation in Fiqh education at MTs Al-Mukarrom Ponorogo. (2) To describe the implementation of summative evaluation in Fiqh education at MTs Al-Mukarrom Ponorogo. (3) To identify the obstacles in the implementation of these evaluations and find solutions. This research uses a qualitative method by conducting direct interviews with teachers and students. The data collection techniques used are direct interviews and observations. The results of this study indicate that the summative and formative evaluation programs at MTs Al-Mukarrom Ponorogo have been implemented in accordance with the program formulated by the school. Summative evaluation at MTs Al-Mukarrom is conducted through end-of-semester exams designed to measure students' understanding of the material taught over the semester. Formative evaluation, on the other hand, is applied continuously during the learning process. Teachers use various methods such as quizzes, class discussions, and daily assignments to monitor student progress and provide constructive feedback. The challenges faced in implementing these evaluations include time constraints, lack of resources, and variations in student abilities. The solutions offered include teacher training to improve evaluation skills, the use of technology for efficiency, and a more personalized approach in providing feedback to students.